Cloning of lipase cDNA from Olea europaea cv. Gemlik leaves and expression analysis in response to cold stress - Yurtsever, Munise; Vural Korkut, Senay (Tubitak Scientific & Technological Research Council Turkey, 2019)
The cDNA encoding lipase enzyme was cloned from Olea europaea var. europaea cv. Gemlik leaves using the RACE method. The full nucleotide sequence was 1546 bp long and encoded a putative protein of 412 amino acid long protein. The amino acid sequence showed identity to Triacylglycerol Lipase 1 sequences from different plants. A phylogenetic tree was constructed showing relations with various plant lipases. Multiple sequence alignment analysis of the putative protein sequence revealed that the enzyme contains conserved GXSXG pentapeptide motif, and the catalytic triad was predicted as Ser-182, His-379, and Asp-350 with bioinformatics tools. Real-time PCR was used to determine relative expression levels of lipase in leaves in response to cold stress.
Keywords: Lipase; olive; RACE; stress; real-time PCR; TRIACYLGLYCEROL LIPASE; GENE; PURIFICATION; FAMILY; OIL; Plant Sciences